2000
DOI: 10.1109/75.842070
|View full text |Cite
|
Sign up to set email alerts
|

Low-loss distributed MEMS phase shifter

Abstract: This letter presents a one-bit low-loss-band phase shifter circuit that employs microelectromechanical systems (MEMS) capacitors. The measured results demonstrate a delay line with a 180 phase shift/1.17 dB loss phase shift at 25 GHz, 270 phase shift/1.69 dB loss at 35 GHz, and a return loss better than 11 dB over a 0-35-GHz band. The state-of-the-art insertion loss performance, 154 /dB at 25 GHz and 160 /dB at 35 GHz, demonstrates the potential for the implementation of a very low-loss multibit digital MEMS p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
39
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(40 citation statements)
references
References 15 publications
1
39
0
Order By: Relevance
“…By applying a single bias voltage to either the signal conductor of the CPW line or the MEMS bridges lying over this centre conductor, the effective distributed capacitance of the line can be changed, which in turn changes the phase velocity and, thus, the associated propagation delay through the transmission line. Using this principle, Borgioli et al [44] reported a 1-bit ultra-wide bandwidth distributed loadedline. Again, MEMS capacitive membrane switches were employed, with C ON /C OFF B7.5 and having an actuation voltage of 75 V. Here, an 8.6 mm long CPW line on a glass substrate achieved a DC to 35 GHz bandwidth, with a relative phase shift and insertion loss of 2701 and 1.7 dB, respectively, at 35 GHz.…”
Section: Phase Shiftersmentioning
confidence: 99%
“…By applying a single bias voltage to either the signal conductor of the CPW line or the MEMS bridges lying over this centre conductor, the effective distributed capacitance of the line can be changed, which in turn changes the phase velocity and, thus, the associated propagation delay through the transmission line. Using this principle, Borgioli et al [44] reported a 1-bit ultra-wide bandwidth distributed loadedline. Again, MEMS capacitive membrane switches were employed, with C ON /C OFF B7.5 and having an actuation voltage of 75 V. Here, an 8.6 mm long CPW line on a glass substrate achieved a DC to 35 GHz bandwidth, with a relative phase shift and insertion loss of 2701 and 1.7 dB, respectively, at 35 GHz.…”
Section: Phase Shiftersmentioning
confidence: 99%
“…In DMTL phase shifters small phase shift can be achieved with high accuracy. Demonstrated DMTL phase shifters on fused silica (McFeetors and Okoniewski 2006), high resistivity silicon (Palei et al 2005;Lakshminarayan and Weller 2002), low resistivity silicon (Wang et al 2008;Guo et al 2006), or ceramic substrates such as quartz (Hayden and Rebeiz 2003Weller 2007, 2006; Rebeiz 2000, 1998;Fangmin et al 2001), Pyrex glass Borgioli et al 2000;Topalli et al 2006), use highly sophisticated and expensive silicon microfabrication process technologies. RF devices have also been demonstrated with several non-conventional processes on microwave laminates with emphasis on the performance improvement in insertion loss at the cost of fabrication complexity (Ramadoss et al 2005).…”
Section: Introductionmentioning
confidence: 98%
“…Digital phase shifters with this approach allow large phase shift and low sensitivity to electrical noise. In the published CPW digital phase shifters [4,5], a small metalinsulator-metal (MIM) capacitor or metal-air-metal (MAM) [10,11] in series with the MEMS bridge capacitor was used to reduce the total shunt capacitance seen by the line, resulting in an acceptable return loss for both switching states over a wide band.…”
Section: Introductionmentioning
confidence: 99%
“…However, since there was a limit on the control range of the bridge height before the bridge snaps, the analog phase shifter showed relatively small phase shift. This problem was solved by operating the MEMS bridges in the digital mode [4][5][6][7][8][9][10][11], where two distinct capacitance states (ON and OFF) were defined with a high ratio. Digital phase shifters with this approach allow large phase shift and low sensitivity to electrical noise.…”
Section: Introductionmentioning
confidence: 99%